STRATEGIC INITIATIVES BY THE INDONESIAN CONSULATE GENERAL IN DAVAO CITY TO STRENGTHEN BILATERAL TOURISM TIES BETWEEN INDONESIA AND THE PHILIPPINES - Putri, Juniya Olgalia; Nur Azizah; Umi Yanti Febriana Silalahi (Journal of Social Politics and Governance (JSPG), 2025)
Tourism diplomacy plays a vital role in strengthening paradiplomatic ties between regions, particularly in archipelagic and culturally connected nations like Indonesia and the Philippines. However, there remains a significant gap between diplomatic efforts and practical outcomes, especially in the context of enhancing cross-border tourism between North Sulawesi and Mindanao. This study aims to examine the tourism diplomacy techniques (Strategies) employed by the Consulate General of the Republic of Indonesia (CJRI) in Davao City to foster paradiplomatic cooperation. Utilizing a mixed methods approach with an exploratory sequential design, qualitative data were collected through literature reviews and semi-structured interviews with diplomats at CGRI Davao, while quantitative data were obtained from secondary sources, including the Statistics Bureau (BPS) of North Sulawesi and the Department of Tourism (DOT) of the Philippines. The findings reveal that CGRI Davao has implemented multiple strategies, such as collaborations with travel agencies, participation in international cultural events, and efforts to restore direct air and sea links. These findings serve as a reference for developing more integrated and impactful paradiplomatic tourism strategies in the future.